Adherence to the Mediterranean diet in two Moroccan populations living at different distances from the Mediterranean Sea - Mohamed Mziwira; Houda Elfane; Sanaa El-Jamal; Imane Barakat; Khadija Sahel; Adil Kalili; Rachida Moustakim; Rachida El-Ouaf; Nadia El-Mahri; Kaoutar Naciri; Loubna Arkoubi Idrissi; Naima Errabahi; et al. (National Institute of Public Health - National Institute of Hygiene, 2024)
Background. There is growing strong scientific evidence over the past few decades that the Mediterranean diet (MD) has protective effects on cardiometabolic health. Objective. This study aimed to assess MD adherence and its association with sociodemographic and lifestyle factors among women living in two Moroccan provinces, El Jadida and Tetouan, located at different distances from the Mediterranean Sea. Material and methods. It is a cross-sectional study involved 355 subjects of which 55.8% reside in the province of El Jadida, and data on socio-demographic characteristics, lifestyle, cardiovascular risks, medical history and of food frequency consumption were collected. Compliance with the MD was assessed with a simplified MD adherence score based on the weekly frequency of consumption of eight food groups. Results. The overall mean Simplified Mediterranean Diet Score was 4.37 ± 1.47 with inadequate compliance in 55.2% of the sample. No significant association was found between adherence to MD and geographic, socio-demographic, lifestyle or the major cardiovascular risk factors. However, the participants do not comply with half of the recommendations based on the Mediterranean diet pyramid. The lowest level of compliance was observed for olive oil, followed by sweets, eggs, potatoes, fruits, red meat, vegetables, legumes, olives, nuts and seeds. The increased contribution of sugars, dairy products and meat to the overall food intake is significant in the category with high adherence to MD. Conclusion. The study data indicate that Mediterranean Diet is far from being a global pattern in this Moroccan population. The study draws attention to the need for a promoting intervention to maintain this pattern as the original diet in the region.